Analytical Studies on Levels of Thermal Comfort in Typical Low-Income Houses Design - Ibrahim, S.H.; Baharun, A.; Mohd Nawi, M.N.; Junaidi, E. (Journal of Civil Engineering, Science and Technology, 2014)
This paper investigates the present situation of thermal comfort in typical low-income houses located in Betong and Saratok, Sarawak, Malaysia. Investigations were carried out by measuring airflow rate, temperature, relative humidity and mean radiant temperature at specific points in one chosen house of each district. Different low-income housing estates were chosen for comparisons due to the different location and position of each house. Although both of these low- income houses have similarity in design but differs in layout arrangement. Results are presented and analyzed using Corrected Effective Temperature (CET) index in two different window and door opening configurations. The results show that the modern low-income house is thermally uncomfortable under certain conditions. High internal air temperatures occurred when doors and windows were closed combined with low air velocity contributes to thermally uncomfortable environment. Once all doors and windows were opened, allowing the air movement to increase, thermal comfort was achieved although air temperatures remained high.